Technology, Innovation and Information in Education - Gafforov, Yarash Xolliyevich (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents information on information, technologies and innovation of the educational process. In particular, the rapid development of science and technology is covered by reforms in the field of education in the field of education of society.